Pharmacoeconomic evaluation of antimicrobial wound dressings in the treatment of venous leg ulcers - Dimitrić, Dragana; Bogavac Stanojević, Nataša; Krajnović, Dušanka; Lakić, Dragana (Archives of Pharmacy, 2025)
Venous leg ulcers (VLUs) account for most lower extremity wounds. Wound management include cleansing, debridement, infection control and applying wound dressing. There exist various types of dressings which can maintain adequate moisture, offer protection, and support the reepithelization of VLUs. The aim of this study is to evaluate the cost-effectiveness of the antimicrobial wound dressing containing ionic silver (AquacelÒ Ag+ExtraTM) in the treatment of VLUs compared to conventional gauze dressing in Serbia. The data regarding the effectiveness and frequency of dressings for both the AquacelÒ Ag+ExtraTM and conventional dressing were obtained from literature sources. Only direct costs were considered, and values were taken from the published price list of health services or procurement procedures. Sensitivity analyses were performed.  The total cost per patient for AquacelÒ Ag+ExtraTM was 34,178.76 RSD, while the total cost for gauze was 82,800.90 RSD. Besides lower costs, antimicrobial wound dressing shows higher effectiveness than the gauze, implying that AquacelÒ Ag+ExtraTM is the dominant strategy. The sensitivity analysis supports the robustness of the results.  The use of antimicrobial wound dressing containing ionic silver is the preferred option for the treatment of VLUs due to lower costs and the higher curing rate of the wounds.
Keywords: dressing; economic evaluation; venous leg ulcer; cost-effectiveness